Agrobacterium-Mediated Transformation of the Aquarium Plant Cryptocoryne willisii with Gus and gfp Genes - Khalid, N.; Wong, S.M.; Sahidin, N. (2010)
The effects of different infection times (2, 4, 6, 8, and 10 min) and co-cultivation periods (1, 2, 3, and 4 days) on transformation ofCryptocoryne willisii with Agrobacterium tumefaciens strain LBA4404 harbouring pCAMBIA1304 were assessed. Fluorometric assay revealed that the highest expression of β-glucuronidase (GUS) enzyme driven by the CaMV 35S promoter can be achieved by 6 min infection time and one day of co-cultivation (582.1 ± 84.3 pmol 4MU/mg/min). Expression of green fluorescent protein (mgfp5) gene fused to 5' GUS gene was also observed. Transformants appeared green fluorescent under ultraviolet light (UV) excitation. Plantlets of C. willisii showing GFP positive results were subjected to molecular analysis. Polymerase chain reaction (PCR) and Southern blot analysis confirmed the transformation event of individual regenerated plantlets. For direct shoot regeneration, 6 mg·L -1 6-BA supplemented Murashige and Skoog medium was optimal and was then subsequently used for regeneration and propagation of transformed C. willisii. Shoot proliferation and elongation were achieved on a single medium without the need for subculturing.